FRI0562 Proportion of hip and non-hip major fractures: costs and quality of life. (15th June 2017) - Marques, ML; Marques, A; Daniel, A; Brites, L; Silva, JAP da
Abstract : Background: FRAX® country specific risk estimates are a mainstay of current treatment decisions and public health policies in osteoporosis. Because the registries of major non-hip fractures (NHF) is poor in most countries, this estimate is based on the gender- and age-specific ratio of hip fractures (HF) to NHF observed in a prospective population-based study performed in Malmo, Sweden 1 . FRAX® presumes, therefore, that the ratio of incidence and cost of hip/major osteoporotic fractures is similar, in every country, to that observed in Sweden. This major assumption has seldom been questioned. Objectives: This retrospective single-centre observational study aimed to assess the proportion of HF vs. NHF and the impact of wrist and vertebral fractures, in terms of costs and health-related quality of life (HrQoL), 1 year after the fracture in Portugal. Methods: We revised the records of all patients observed in an emergency department through a period of 3 months and included those aged 50+ diagnosed with a fragility (low energy) HF or NHF. A telephone interview was conducted in a randomly selected subsample of patients from each type of fracture 1 year after fracture. A questionnaire with socio-demographic data, resource consumption over 1st year and HrQol (EQ-5D) was applied to patients or their caregivers. Direct and indirect costs were estimated from a societal perspective. Results: In the study period, 1760 patients were observed by the orthopaedics emergency team. Of these, 435 patients had suffered a fracture (129 fragility HF, 152 NHF and 154 fractures that were not considered low-trauma and were therefore excluded). Humerus fractures were also excluded, to mirror the Swedish study. The randomly selected subsample of patients consisted of 66 NHF (55 with wrist and 11 with clinical vertebral fractures). Patients were mostly females in all types of fractures (58% to 82%). The mean age at fracture was higher in HF (81.6±8.59 vs. 69.1±10.06). Falls were the cause of fracture in 97% of cases. Inpatient care was provided to 100% of HF patients vs. 25.8% of NHF patients. The proportion of fractures, average fracture-related costs for the 1st year, and the mean impact upon HrQoL are shown in Table 1 . Conclusions: The proportion HF/NHF observed in Portugal is similar to the Swedish reference values (0.44/0.56). The highest cost were attributed to hip fractures in both countries, followed by vertebral fractures and lastly by wrist fractures. The HrQoL mean loss was higher for vertebral fractures in both countries. The reported costs of vertebral fractures are much higher than in Portugal which may significantly affect the calculation of cost-effectiveness thresholds for intervention. References: Borgström F, et al. Osteoporos Int. 2006;17(5):637–50. Marques A, et al. Osteoporos Int. 2015 Nov;26(11):2623–30. Disclosure of Interest: None declared